Regulator of G-Protein Signaling (RGS) Protein Modulation of Opioid Receptor Signaling as a Potential Target for Pain Management - Senese, Nicolas B.; Kandasamy, Ram; Kochan, Kelsey E.; Traynor, John R. (Frontiers in Molecular Neuroscience, 2020)
Opioid drugs are the gold standard for the management of pain, but their use is severely limited by dangerous and unpleasant side effects. All clinically-available opioid analgesics bind to and activate the mu-opioid receptor (MOR), a heterotrimeric G-protein-coupled receptor, to produce analgesia. The activity of these receptors is modulated by a family of intracellular RGS proteins or regulators of G-protein signaling proteins, characterized by the presence of a conserved RGS Homology (RH) domain. These proteins act as negative regulators of G protein signaling by serving as GTPase accelerating proteins or GAPS to switch off signaling by both the G and  subunits of heterotrimeric G proteins. Consequently, knockdown or knockout of RGS protein activity enhances signaling downstream of MOR. In this review we discuss current knowledge of how this activity, across the different families of RGS proteins, modulates MOR activity, as well as activity of other members of the opioid receptor family, and so pain and analgesia in animal models, with particular emphasis on RGS4 and RGS9 families. We discuss inhibition of RGS proteins with small molecule inhibitors that bind to sensitive cysteine moieties in the RH domain and the potential for targeting this family of intracellular proteins as adjuncts to provide an opioid sparing effect or as standalone analgesics by promoting the activity of endogenous opioid peptides. Overall, we conclude that RGS proteins may be a novel drug target to provide analgesia with reduced opioid-like side effects, but that much basic work is needed to define the roles for specific RGS proteins, particular in chronic pain, as well as a need to develop newer inhibitors.